Anti-Convulsant Activity of Ethanolic Extract of Ofalternanthera Sessilis on Phenytoin Induced Memory Impairment In Rats - Myreddy, Jayasree; Ashok, Purnima; P, Rajani G; Cheruku, Anusha; Chavva, Pavitra (Asian Journal of Pharmaceutical Research and Development, 2014)
Alternantherasessilis grows widely in the areas tropical regions, mainly found in tropical America, Africa and Asia. It contains many active constituents like flavonoids, steroids, saponins, glycosides, terpinoids, carbohydrates, phenols and tannins. It is reported to have anti-inflammatory, hepatoprotective, hematinic, anti-ulcer, antioxidant, antidiabetic activities.1 The present study was aimed at evaluating the ethanolic extract ofAlternantherasessilislinn, at doses of 200 and 400mg/kg for Anticonvulsant activity. Anticonvulsant activity of the ethanolic extract of the Alternantherasessilis (ASE 200 and 400mg/kg) was evaluated by Electric shock induced convulsions in Group I,II,III, IV,V,VI,VII and VII animals Group I was taken as control (saline),Group II was taken as Standard Phenytoin (25mg/kg b.w.),Group III& IV received the high and low doses of Ethanolic extract (200& 400 mg/kg b.w.), Group V was treated with piracetam(200 mg/kg b.w.),Group VI & VII treated with Phenytoin and in combinations of high and low doses of Ethanolic extract (200 & 400 mg/kg b.w.) and Group VIII was treated with phenytoin and piracetam in combination. Anticonvulsant activity was evaluated by the time spent by the animal in different stages of convulsions (tonic flexion, tonic extensor, clonic convulsions, stupor, recovery or death).Ethanolic extract of Alternantherasessilis at both the doses produced significant anticonvulsant activity when evaluated by determining time spent by animal in different stages of convulsions. Interpretation of the results was done after subjecting the data obtained from various studies to statistical analysis which included one way ANOVA followed by post test (Tukey’s). The results suggest that the whole plant of Alternantherasessilis possess memory enhancing activities.